PERANCANGAN APLIKASI PENGOLAHAN DATA PENJUALAN UKM KELANTING KHAS TELO DESA SIDOHARJO KECAMATAN JATI AGUNG KABUPATEN LAMPUNG SELATAN - Febriani, Ochi Marshella; Ambarwati, Laili (Jurnal Teknologi Informasi dan Bisnis Pengabdian Masyarakat Darmajaya, 2015)
sidoharjo Village located in jati agung south lampungÂ  with livelihoods agriculture , among other agricultural products produced namely palm oil , corn , cassava .But , there are still many obstacles that arise because there is no information systems that helps in terms of the data processing the sales profits from products in this area .This village to develop their region , with transaction perform the process of buying and selling of cassava processed in the form of the processed products , namely kelanting .This new product affect the level of sales and earnings sidoharjo village .Therefore to ease to the process of necessary data processing an application that can be help in processing the data of selling transaction a product with using media programming .For it in supporting all activites of transactions above the application of what it needs is visual basic using a storage medium , seen from the data collection method and processes transactions / input an output that easy for the user . Keywords : application design, system design, visual basic